Communication Skills and Timely Delivery of NGO Projects in Lagos State: A Study of Female Project Managers - Riyanat Olasumbo Tiamiyu; Yusuf Adedayo Lawal; Segun Oluwaseun Olabode (Applied Quantitative Analysis, 2024)
The timely delivery of projects is a critical factor in the success of nongovernmental organizations (NGOs), particularly in dynamic environments like Lagos State, Nigeria. However, many NGOs face challenges in meeting project deadlines because of ineffective communication among project managers. This study specifically focuses on female project managers because they have been shown to bring unique perspectives to project management, yet their role in the timely delivery of NGO projects has been underexplored. This study examined the influence of female project managers’ communication skills on the timely delivery of NGO projects in the Alimosho Local Government Area of Lagos State. Adopting a survey research design, the study targeted female project managers at NGOs, with a sample size of 57, of which 49 valid responses were used for analysis. The study employed a questionnaire as the primary research instrument, and the reliability of the instrument was assessed using a test-retest method, while content and face validity were used to measure its validity. A simple linear regression analysis was used to test the hypothesis. The results revealed a significant positive relationship between female project managers’ communication skills and timely delivery of NGO projects (R² = .590, p-value = .000). The findings highlight the critical role of communication skills in ensuring the success of NGO projects. Based on these results, it is recommended that NGOs in Lagos State prioritize the development and enhancement of communication skills in female project managers through targeted training programs, enabling them to navigate project complexities, foster collaboration, and ultimately achieve more timely and impactful project outcomes that contribute to sustainable social change within their communities.